Transcranial Doppler Ultrasonography as a Diagnostic Tool for Cerebrovascular Disorders - Pan, Yuanmei; Wan, Wenbin; Xiang, Minjie; Guan, Yangtai (Frontiers in Human Neuroscience, 2022)
Imaging techniques including transcranial Doppler (TCD), magnetic resonance imaging (MRI), computed tomography (CT), and cerebral angiography are available for cerebrovascular disease diagnosis. TCD is a less expensive, non-invasive, and practically simpler approach to diagnosing cerebrovascular disorders than the others. TCD is a commonly available and inexpensive diagnostic tool. However, owing to its large operator dependency, it has a narrow application area. Cerebrovascular disease refers to a group of disorders that alter blood flow in the brain. The brain's functions can be temporarily or permanently impaired as a result of this change in blood flow. Timely diagnosis and treatment can restore the brain-impaired functions, resulting in a much-improved prognosis for the patients. This review summarizes the basic principles underlying the TCD imaging technique and its utility as a diagnostic tool for cerebrovascular disease.